2003
DOI: 10.1177/108471380300700402
|View full text |Cite
|
Sign up to set email alerts
|

Hearing Aid Satisfaction: What Does Research from the Past 20 Years Say?

Abstract: Hearing aid satisfaction is a pleasurable emotional experience as an outcome of an evaluation of performance. Many tools have been designed to measure the degree of satisfaction overall, or along the dimensions of cost, appearance, acoustic benefit, comfort, and service. Various studies have used these tools to examine the relationships between satisfaction and other factors. Findings are not always consistent across studies, but in general, hearing aid satisfaction has been found to be related to experience, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
80
1
5

Year Published

2005
2005
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 97 publications
(94 citation statements)
references
References 66 publications
8
80
1
5
Order By: Relevance
“…It appears that use and satisfaction represent different dimensions of hearing aid outcome. Other studies have reported correlation coefficients varying between -.24 to .66 (Wong et al, 2003). The correlation between hearing aid use (days per week) and satisfaction in this study was relatively low (r=0.25; additional analysis, not yet reported).…”
Section: Degree Of Hearing Losscontrasting
confidence: 57%
“…It appears that use and satisfaction represent different dimensions of hearing aid outcome. Other studies have reported correlation coefficients varying between -.24 to .66 (Wong et al, 2003). The correlation between hearing aid use (days per week) and satisfaction in this study was relatively low (r=0.25; additional analysis, not yet reported).…”
Section: Degree Of Hearing Losscontrasting
confidence: 57%
“…Hearing aid and other assistive devices are prerequisite for many subsequent interventions such as communication strategy programmes or hearing aid counseling programmes (Abrams et al, 2002;Chisolm et al, 2004;Saunders & Forsline, 2012). Even though assistive devices provide sophisticated solutions for amplifying residual hearing, background noise remains one of the most significant barriers to hearing aid use and satisfaction (Kochkin, 2000;Wong et al, 2003). Expert responses corresponded with this phenomenon with 82.5% indicating this category.…”
Section: Several Categories Also Belonged To Chapter 8 Major Life Armentioning
confidence: 99%
“…These features can offer advantages in many difficult listening situations, but the scientific evidence that they produce a significant increase in the satisfaction of hearing aid users is still fairly weak (Wong et al, 2003). It is also clear that modern hearing aids and fit- Figure 1.…”
Section: Introductionmentioning
confidence: 99%